OS07.3.A Phase 1/2 clinical trial of blood-brain barrier opening with the SonoCloud-9 implantable ultrasound device in recurrent glioblastoma patients receiving IV carboplatin. (5th September 2022) - Idbaih, A; Sonabend, A; Stupp, R; Chinot, O; Dufour, H; Ducray, F; Menei, P; de Groot, J; Desseaux, C; Carpentier, A
Abstract: Background: Low intensity pulsed ultrasound (LIPU) in combination with microbubbles is a promising approach for brain drug delivery. A phase 1/2 clinical study (NCT03744026) was initiated to demonstrate the safety and efficacy of blood-brain barrier (BBB) disruption over a large volume using an implantable ultrasound system (SonoCloud-9) in patients with recurrent glioblastoma receiving carboplatin chemotherapy. Material and Methods: The SonoCloud-9 device (Carthera, Paris, France) was placed at the end of tumor resection and replaced the bone flap. The device was activated 9-14 days after surgery for a duration of 270 seconds every 4 weeks until progression or treatment completion, concomitantly with IV DEFINITY microbubbles (10 μl/kg, Lantheus, Billerica, US). The Phase 1 cohort consisted of an escalation of BBB disruption volume by activation of 3 (n=3), 6 (n=3), then 9 (n=3) emitters of the device. Dose limiting toxicity (DLT) was assessed during the first 2 weeks after the 1st sonication. A subsequent expansion cohort consisted of patients treated with 9 emitters in which the primary endpoint was assessment of BBB opening on MRI using gadolinium (<1 hr after sonication). All patients received carboplatin either after (n=21) or before (n=12) device activation to disrupt the BBB. In addition, a sub-study was performed to investigate carboplatin concentration enhancement in the peritumoral region with sonication at time of device implantation. Results: Study accrual is complete with 38 patients enrolled and 33 patients having been implanted and received at least one sonication+carboplatin. A total of 101 sonications were performed (range=1-10 sonication sessions/patient). No DLTs were observed. A total of 14 SAEs were observed including five events considered as possibly treatment related. BBB disruption was confirmed by gadolinium enhancement after sonication. In an analysis of 60 treatments in 27 patients that had all nine emitters active, 90% of activated emitters led to BBB opening in gray and/or white matter with good repeatability of BBB opening. In 3 patients who underwent intraoperative sonication and carboplatin administration, a 7.58-fold increase in brain/plasma drug levels was demonstrated. Updated and mature outcome results will be presented. Conclusion: These results confirm the safety and feasibility of repeated BBB disruption using an implantable ultrasound system. LIPU substantially increases drug levels in the peritumoral brain.